RELATIONSHIP BETWEEN COMPENSATION, WORK ENVIRONMENT, ORGANIZATIONAL CULTURE, AND EMPLOYEE PERFORMANCE AT HOTEL SEDONA MANADO - Golung, Hana D. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
ABSTRACT Â  The Indonesian people have more problems in the future human resource development or more specifically on improving the quality of human resources in the current era globalization. This makes company looking for an effective way to solve the human resource issues especially in employee performance. Hotel Sedona Manado is one of the companies that faced the employee performance. This research is to examine the influence of employee performance at Hotel Sedona Manado. Discriminant analysis is a statistical technique that being used in this research analysis. Compensation, work environment, organizational culture, and employee performance are the variables that used in this research. The population is people who work at Hotel Sedona Manado, with the sample size 60 respondents. The result of this research shows that both high performance and low performance employee of Hotel Sedona Manado has a significant differences, which compensation as the most dominant variable in discriminating employee performance, followed by work environment and organizational culture. Keywords: compensation, work environment, organizational culture, employee performance.